A pilot randomized controlled trial of a tailored cognitive behavioural therapy based intervention for depressive symptoms in those newly diagnosed with multiple sclerosis. Issue 1 (December 2016) - Kiropoulos, Litza; Kilpatrick, Trevor; Holmes, Alex; Threader, Jennifer
Abstract Background To examine the effectiveness and acceptability of an 8-week individual tailored cognitive behavioural therapy (CBT) intervention for the treatment of depressive symptoms in those newly diagnosed with multiple sclerosis. Methods The current study presents a pilot, parallel group randomized controlled trial (RCT) with an allocation ratio of 1:1 conducted in a large research and teaching hospital in Melbourne, Australia. 30 individuals with a mean age of 36.93 years (SD = 9.63) who were newly diagnosed with multiple sclerosis (MS) (X = 24.87 months, SD = 15.61) were randomized to the CBT intervention (n  = 15) or treatment as usual (TAU) (n  = 15). The primary outcome was level of depressive symptoms using the Beck Depression Inventory-II (BDI-II). Secondary outcomes were level of anxiety, fatigue and pain impact, sleep quality, coping, acceptance of MS illness, MS related quality of life, social support, and resilience. Tertiary outcomes were acceptability and adherence to the intervention. Results Large between group treatment effects were found for level of depressive symptoms at post and at 20 weeks follow-up (d  = 1.66–1.34). There were also small to large group treatment effects for level of anxiety, fatigue and pain impact, sleep quality, MS related quality of life, resilience, and social support at post and at 20 weeks follow-up (d  = 0.17–1.63). There were no drop-outs and participants completed all treatment modules. All participants reported the treatment as'very useful ', and most (73.4%) reported that the intervention had addressed their problems'completely' . Conclusions These data suggest that the tailored early intervention is appropriate and clinically effective for the treatment of depressive symptoms in those newly diagnosed with MS. A larger RCT comparing the CBT intervention with an active comparative treatment with longer term follow-up and cost effectiveness analyses is warranted. The pilot trial has been retrospectively registered on 28/04/2016 with the ISRCTN registry (trial ID ISRCTN10423371).